PENGARUH SENAM ERGONOMIK TERHADAP PENURUNAN KADAR ASAM URAT PADA LANSIA DI DUSUN 1 MEDAN ESTATE - Derma Gawati Lumbantoruan; Mhd. Taufik Daniel Hasibuan (Universitas Murni Teguh, 2026)
Older adults are a population group that is vulnerable to increased uric acid levels due to the aging process accompanied by decreased metabolic function and renal excretion. Elevated uric acid levels can cause joint pain, limited physical activity, and a decline in the quality of life of older adults. One non-pharmacological intervention that can be applied to help reduce uric acid levels is ergonomic exercise. This study aimed to determine the effect of ergonomic exercise on reducing uric acid levels in older adults in Dusun I Medan Estate. This study employed a pre-experimental design with a one-group pretest–posttest approach. The sample consisted of 13 older adults selected using a total sampling technique. The ergonomic exercise intervention was carried out regularly according to standard operating procedures. Uric acid levels were measured before and after the intervention. Data were analyzed using univariate and bivariate analysis, including the Shapiro–Wilk normality test and the Wilcoxon Signed Rank Test. The results showed a significant decrease in uric acid levels after the ergonomic exercise intervention, with a p-value of 0.002 (p < 0.05). It can be Conclusion: that ergonomic exercise has a significant effect on reducing uric acid levels in older adults in Dusun I Medan Estate. Suggestions: Future studies are recommended to use a quasi-experimental design with a control group, a larger sample size, and a longer intervention duration to evaluate long-term effects.